Market potential of value added coconut products - Sali K S (Department of Rural Marketing Management, College of Co operation Banking and Management, 2006)
In India, due to multifaceted uses, coconut is referred as ‘Kalpavriksha’ and provides livelihood to more than 10 million people. Among the major coconut growing states in India, Kerala enjoys the pride of place both in area and production of coconut. However, there is a trend for reduced farm income due to fluctuating prices. Therefore, the coconut industry and the farmers depending on them are striving to survive in the economy. In this scenario, best option appears to be diversification and value addition. In this context, present study was undertaken with the following objectives: 1. to measure the market awareness of value added coconut products; 2. to examine the customers perception towards selected value added coconut products; and 3. to assess the market potential for selected value added coconut products. For the study, four divisions from Thrissur Corporation area were selected randomly. A sample of 100 households, 25 from each division were randomly selected. The selected products were coconut oil, coconut milk, coconut milk powder, coconut palm jaggery, coconut chips, coconut vinegar, elaneer soda and neera. The study was mainly based on primary data collected from the sample respondents through personal interview method by administering a pre-tested structured schedule. The data thus obtained were analysed by using the tools like bivariate table, percentages, ranking, regression and indices. The study revealed that the newly designed and launched products failed to attract the customers attention. It was also revealed that at present the role of advertisement is negligible in creating awareness. The shopkeepers and friends and relatives were considered as the most important sources of information regarding the products. In the perception analysis, it was found that majority of the respondent have least favourable perception towards various attributes of the products because many respondents are not aware about the products or they are ignorant about the attributes of the products. The study revealed that coconut oil has high market potential. But the market potential of coconut milk and coconut milk powder were very low. At the same time, coconut chips and coconut vinegar showed a high market potential eventhough the awareness is less. In the case of elaneer soda and neera, both awareness and market potential found to be very low.